The Influence of Financial Literacy and Income on Investment Decisions: A Case Study of MSMEs in Medan City - Rudianto, Rudianto; Farrell , Edric; Khana Saputri; Pasaribu , Lidya Natalia (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of financial literacy and income on investment decisions among 182 MSME actors in Medan City using a quantitative approach. Data were collected via questionnaires and analyzed through model evaluation, structural analysis, and effect size measurement. Results show that financial literacy significantly affects investment decisions (f² = 0.777), explaining 77.7% of the variance. Income also contributes (f² = 0.170), accounting for 17% of the variance. The remaining 5.3% is attributed to other factors beyond the study’s scope.